Comparison of Two Advection-Diffusion Methods for Tephra Transport in Volcanic Eruptions (Communications in Computational Physics, 2020)
In order to model the dispersal of volcanic particles in the atmosphereand their deposition on the ground, one has to simulate an advection-diffusion-sedimentationprocess on a large spatial area. Here we compare a Lattice Boltzmannand a Cellular Automata approach. Our results show that for high Peclet regimes, thecellular automata model produce results that are as accurate as the lattice Boltzmannmodel and is computationally more effective.